Synthesis method of chabazite with CHA structure
By using the mixed reaction of NaY molecular sieve guide agent and potassium hydroxide without adding organic substances, a chabazeite with a CHA structure was successfully prepared, which solved the problems of high cost and long time in the prior art, and achieved low cost. Synthesis of CHA molecular sieve in a short time.
Patent Information
- Application Number
- CN202310865006.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-07-14
AI Technical Summary
The existing CHA molecular sieve synthesis methods have problems such as high raw material cost, unenvironmental protection and long crystallization time.
By using a method without adding organic substances, the silicon source and aluminum source are mixed with sodium hydroxide and aged to form a NaY molecular sieve guide agent, and then mixed with potassium hydroxide to crystallize to prepare a chazeite with CHA structure, and control the Molar ratios and conditions to achieve low cost synthesis in a short time.
The synthesis of CHA molecular sieve without transcrystallization or seed crystals is achieved, which simplifies steps, reduces costs, and shortens crystallization time. The product has an eight-membered ring structure, which is easy to operate and control.
Smart Images

Figure CN119306228A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of molecular sieve preparation, and in particular to a method for synthesizing chabazite with a CHA structure. Background Art
[0002] CO 2 Large-scale capture, separation and recycling of CO is one of the major issues of concern to human society and is also one of the "seven major chemical separation issues that can change the world". 2 The only method is amine solution absorption, but this technology is highly corrosive to equipment, consumes a lot of regeneration energy, and the amine adsorbent is easily deactivated. Therefore, a method that can separate CO efficiently and at low cost has been developed. 2 New technologies and new materials are very important.
[0003] Type A molecular sieve and type X molecular sieve are widely used adsorbents. 2 The adsorption of H 2 O、CH 4 、N 2 In the presence of small molecules such as CO 2 The adsorption selectivity of CO is not satisfactory. 2 In the adsorption field, in recent years, people have paid extensive attention to and invested a lot of energy in the research and development of small-pore molecular sieves, such as CHA and RHO. These 8-membered ring small-pore molecular sieves with cage-like structures have good adsorption performance on CO. 2 There are special separation mechanisms (size screening, kinetic screening, weak interactions based on physical adsorption, interactions based on chemical adsorption, molecular valve effects, etc.). Therefore, this type of zeolite molecular sieve material has high efficiency in separating CO 2 effect.
[0004] For example, Chinese patent document CN201980019996.1 discloses a method for synthesizing a transition metal-containing CHA framework structure type zeolite, and an organic template is used in the specific preparation process.
[0005] Chinese patent document CN202010797179.3 discloses a CHA-type chabazite molecular sieve and its synthesis method and application, which belongs to the field of chemical synthesis technology and its application. Specifically, N,N,N-trialkyl-N-phenyl quaternary ammonium salt or quaternary ammonium base compound is used as an organic template to synthesize CHA-type chabazite molecular sieve.
[0006] Chinese patent document CN201610480629.X discloses a method for direct hydrothermal synthesis of medium-aluminum-silicon ratio chabazite. In the reaction of synthesizing chabazite under hydrothermal conditions, no organic template agent and no chabazite seed crystals are added. By adding a weakly alkaline inorganic salt, an aluminosilicate zeolite molecular sieve with a chabazite structure is obtained.
[0007] Chinese patent document CN201610480630.2 discloses a method for synthesizing a zeolite molecular sieve having a chabazite structure. The preparation method is as follows: in the reaction of synthesizing chabazite under hydrothermal conditions, no organic template agent and no chabazite seed crystals are added, and an organic weak base is added to obtain an aluminosilicate zeolite molecular sieve having a chabazite structure and a framework silicon-aluminum atomic molar ratio in the range of 4-40.
[0008] Chinese patent document CN201810031149.4 discloses a method for preparing and using low silicon-aluminum ratio chabazite. The preparation method mainly comprises the following steps: using a silicon source, an aluminum source and an alkali as raw materials, calcining (with high energy consumption) or adding chabazite seeds without adding an organic template, fluoride ions, etc., and crystallizing in a high-pressure reactor to obtain a low silicon-aluminum ratio chabazite with a silicon-aluminum ratio of 1.0 to 2.2.
[0009] Chinese patent document CN201110290616 discloses a method for synthesizing chabazite, which specifically adopts a traditional hydrothermal synthesis method to prepare chabazite by a seed-directed method without adding an organic template.
[0010] Chinese patent document CN202210257343.0 discloses a method for preparing CHA zeolite from bleaching earth, specifically, using powdered bleaching earth, under the action of CHA seed crystals, to obtain the product CHA molecular sieve through hydrothermal crystallization reaction. It includes: (1) selecting powdered bleaching earth; (2) preparing KOH solution; (3) roasting the bleaching earth at high temperature to obtain amorphous powder; (4) adding the roasted bleaching earth to the prepared KOH solution, then adding 1-5% by mass of CHA seed crystals, and uniformly mixing to obtain a new reaction mixture; (5) adding the reaction mixture to a hydrothermal reactor for hydrothermal crystallization reaction; (6) taking out the mixture after the reaction and filtering it, and drying the solid obtained after filtration to obtain the product CHA molecular sieve.
[0011] Chinese patent document CN201610497784.2 discloses a medium silicon-aluminum ratio aluminosilicate chabazite, wherein the silicon-aluminum atomic molar ratio of the aluminosilicate chabazite is 20-40, and the aluminosilicate chabazite is prepared by mixing a compound of an aluminum source and a silicon source with sodium hydroxide, potassium hydroxide, and a buffer in a molar ratio of: Na 2 O:K 2 O: Buffer: Al 2 O3 :SiO 2 :H 2 O=(2-20):(2-20):(2-20):1:(40-80):(300-800), specifically, the compounds of aluminum source and silicon source are uniformly mixed with sodium hydroxide, potassium hydroxide and buffer according to the said molar ratio; aged at room temperature for 0.1-16 hours; then hydrothermally crystallized at 120-150 degrees Celsius for 2 to 5 days; and separated and washed to obtain aluminosilicate chabazite.
[0012] Yin Xiaoyan et al. published an experimental study on the preparation of CHA zeolite by crystallization of FAU zeolite (Plastic Additives, Issue 6, 2018). They first prepared faujasite zeolite molecular sieve FAU by hydrothermal synthesis, and then crystallized it to form CHA zeolite molecular sieve.
[0013] Che Shuai published a paper on the successful synthesis of chabazite with a silicon-aluminum ratio of 2.25 using HY molecular sieve as raw material at 95°C for 15 days (chabazite ion exchange modification and CO 2 Study on adsorption separation performance, Northeastern University, PhD thesis, 2013).
[0014] Chinese patent document CN201010202727.X discloses the formation of pure chabazite by permeation of heterogeneous nucleated T-type zeolite in the absence of an organic template.
[0015] Chinese patent document CN202210612836.1 discloses a method for preparing a low-silicon CHA-type molecular sieve, specifically, mixing a potassium source, a sodium source, a silicon source, an aluminum source and water to obtain an initial gel; then the initial gel is subjected to static hydrothermal crystallization at 140-180°C for 2-6 days to obtain a low-silicon CHA-type molecular sieve.
[0016] Chinese patent document CN202210392986.6 discloses a method for in-situ preparation of high-silicon CHA molecular sieve membrane, which comprises mixing silicon source, alkali source, aluminum source, organic structure directing agent OSDA and water, stirring and aging at room temperature to form a sol; immersing a porous carrier in the OSDA solution, and attaching OSDA to the surface of the porous carrier after drying; placing the porous carrier in a polytetrafluoroethylene-lined high-pressure reactor containing the above-mentioned sol, crystallizing under microwave heating, washing, drying and then calcining to obtain a high-silicon CHA molecular sieve membrane. Among them, the organic structure directing agent OSDA will volatilize during the gelation process, and the synthesized molecular sieve must undergo a calcination process to remove the template agent before it can have a porous structure. The calcination process is generally carried out at high temperature, which is costly, and organic matter and CO will be released during the calcination process. 2 In addition, the microwave heating method is difficult to operate and has high requirements on equipment.
[0017] It can be seen that the existing methods for synthesizing CHA molecular sieves mainly use organic templates, seed crystal method, crystal rotation, and the use of organic weak bases or inorganic weak base salts. However, the use of organic templates pollutes the environment, and organic templates are expensive, and even require high-temperature roasting to remove the template agent, which has high energy consumption. The crystal rotation method requires the pre-prepared FAU zeolite and T-type zeolite crystals to be crystallized under certain conditions to convert them into CHA crystal forms. Although the organic template agent is omitted, the steps are cumbersome and the cost is high. The method of synthesizing using inorganic / organic additives or seed crystals generally has certain requirements for the silicon source, and the crystallization time is also relatively long; and the seed crystal method also requires the pre-preparation of CHA seed crystals, and the steps are cumbersome. Summary of the invention
[0018] The purpose of the present invention is to solve the defects of the prior art methods for preparing CHA molecular sieves, such as high raw material cost, environmental pollution, or long crystallization time, and thus provide a method for synthesizing chabazite with a CHA structure. The method can prepare CHA molecular sieves with eight-membered ring structural units in situ without adding organic substances, and has a short crystallization time, low cost, and easy operation and control.
[0019] To achieve the above object, the present invention provides a method for synthesizing chabazite having a CHA structure, comprising the following steps:
[0020] Step 1, mixing a silicon source and an aluminum source, or a silicon source, an aluminum source and sodium hydroxide, and aging the mixture to obtain a NaY molecular sieve directing agent;
[0021] Step 2, mixing a silicon source, an aluminum source and the NaY molecular sieve directing agent to form a gel;
[0022] Step 3, uniformly mixing the gel and potassium hydroxide, crystallizing, separating and washing to obtain the chabazite having a CHA structure;
[0023] In step 1, the oxide (SiO 2 Calculate the silicon in NaY molecular sieve directing agent; 2 O 3 Calculate the aluminum in NaY molecular sieve directing agent; 2 O is calculated as sodium in the NaY molecular sieve directing agent), and the molar ratio of each substance in the NaY molecular sieve directing agent is (10-18)SiO 2 :(0.7~1.3)Al 2 O 3 :(10~18)Na 2 O: (200~400)H 2 O;
[0024] Calculated as oxide (SiO 2 Calculate the silicon in the gel as Al 2O 3 The aluminum in the gel is calculated as Na 2 O is calculated as sodium in the gel), and the molar ratio of each substance in the gel is (1-6)Na 2 O: (0.7~1.3)Al 2 O 3 :(5~18)SiO 2 :(100~350)H 2 O;
[0025] The mass ratio of the potassium hydroxide to the gel is (6-25):100.
[0026] In the synthesis method of chabazite having a CHA structure provided by the present invention, when controlling the molar ratio of the NaY molecular sieve directing agent and the substances in the gel, if necessary (for example, when industrial standard raw materials are used, the concentrations are limited and the proportions of the materials cannot be accurately regulated), low-basicity sodium aluminate or high-basicity sodium aluminate may be added to adjust the ratio of the materials. If the prepared raw materials are used, low-basicity sodium aluminate or high-basicity sodium aluminate may not be used for adjustment.
[0027] Low basicity sodium aluminate and high basicity sodium aluminate are both raw materials for the industrial synthesis of NaY molecular sieves. Their compositions are Na 2 O、Al 2 O 3 , the concentrations of low-alkalinity sodium aluminate and high-alkalinity sodium aluminate are different.
[0028] Optionally, in the method for synthesizing chabazite having a CHA structure provided by the present invention, the potassium hydroxide is a solid or an aqueous solution thereof. In order to increase the yield, solid potassium hydroxide is preferred.
[0029] Optionally, in step 3 of the method for synthesizing chabazite having a CHA structure provided by the present invention, in order to ensure the uniformity of dispersion of the potassium hydroxide in the gel, the gel and the potassium hydroxide are mixed and stirred for at least 10 minutes.
[0030] Optionally, in the method for synthesizing chabazite having a CHA structure provided by the present invention, the crystallization time is 12 to 35 hours.
[0031] Optionally, in the synthesis method of chabazite having a CHA structure provided by the present invention, the crystallization temperature is 85 to 110° C. The crystallization is carried out in a closed container. If the closed container is resistant to high pressure, the crystallization temperature can be increased to 110° C.; if the closed container is not resistant to high pressure, the crystallization temperature is controlled at 85 to 100° C.
[0032] Optionally, in the synthesis method of chabazite having a CHA structure provided by the present invention, Al 2 O3 The NaY molecular sieve directing agent and the gel are respectively measured, and the mass ratio of the NaY molecular sieve directing agent to the gel is (3-30):100.
[0033] Optionally, in the method for synthesizing chabazite having a CHA structure provided by the present invention, in step 1, the aging temperature is 25 to 40° C., and the aging time is 6 to 42 h, preferably 15 to 40 h.
[0034] Optionally, in the method for synthesizing chabazite having a CHA structure provided by the present invention, in step 2, after the silicon source and the NaY molecular sieve directing agent are mixed, an aluminum source is added at a uniform speed within 0.5 to 4 hours, and after the aluminum source is added, homogenization is performed to obtain the gel.
[0035] Optionally, in the method for synthesizing chabazite having a CHA structure provided by the present invention, in step 2, the aluminum source can be added to the silicon source at a uniform speed within 0.5 to 4 hours, and after the aluminum source is added, the NaY molecular sieve directing agent is added and homogenized to obtain the gel.
[0036] The above homogenization method and parameters are not specifically limited, and conventional methods and parameters in the industry can be used to mix the various substances uniformly. For example, stirring can be selected, and the mixture is stirred for 0.5 to 4 hours until the mixture is uniformly mixed.
[0037] Optionally, in the synthesis method of chabazite having a CHA structure provided by the present invention, the silicon source can be any conventional silicon source in the industry without specific limitation, such as an organic silicon source or an inorganic silicon source. The present invention recommends an inorganic silicon source, preferably at least one of water glass, silica sol and silica gel;
[0038] The aluminum source can be any conventional aluminum source in the industry without specific limitation, and can be selected from an organic aluminum source or an inorganic aluminum source. The present invention recommends an inorganic aluminum source, preferably at least one of aluminum sulfate, sodium aluminate and sodium metaaluminate.
[0039] Optionally, in step 2 of the method for synthesizing chabazite having a CHA structure provided by the present invention, when the silicon source is silica gel, it needs to be dissolved with a sodium hydroxide solution. The concentrations of the silica gel and the sodium hydroxide solution are not specifically limited as long as the molar ratios of the substances in the gel can be satisfied.
[0040] The chabazite with a CHA structure obtained by the synthesis method of the chabazite with a CHA structure provided by the present invention has an eight-membered ring structure, and the synthesis time is short and the cost is lower.
[0041] Compared with the prior art, the present invention has the following advantages:
[0042] The method for synthesizing chabazite with a CHA structure provided by the present invention comprises the following steps: firstly synthesizing a NaY molecular sieve directing agent with a specific ratio, then forming a gel with a specific ratio, and finally adding potassium hydroxide to the gel to directly synthesize a CHA molecular sieve with an eight-membered ring structural unit. The NaY molecular sieve directing agent added during the synthesis of the gel brings about a certain crystal nucleus structure, and the addition of K in step 3 + After the ions are introduced, they will guide the crystal nucleus to generate an octagonal ring structure, and finally form a chabazite with a CHA structure. The synthesis method provided by the present invention does not require crystallization or adding crystal seeds during the entire process, does not require the addition of organic substances, and has a short crystallization time, low cost, and is easy to operate and control. If the ratio of each material in the NaY molecular sieve directing agent or gel is not within the specified range, or the amount of potassium hydroxide added is not within the specified range, the final product is not a chabazite with a CHA structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is an electron microscope image of the chabazite having a CHA structure synthesized in Example 1 of the present invention;
[0044] Figure 2 This is an electron microscope image of the chabazite having a CHA structure synthesized in Example 2 of the present invention;
[0045] Figure 3 This is an electron microscope image of the chabazite having a CHA structure synthesized in Example 3 of the present invention;
[0046] Figure 4 This is an electron microscope image of the chabazite having a CHA structure synthesized in Example 4 of the present invention;
[0047] Figure 5 This is an electron microscope image of the chabazite having a CHA structure synthesized in Example 5 of the present invention;
[0048] Figure 6 This is an electron microscope image of the NaY zeolite with FAU structure synthesized in Comparative Example 1 of the present invention;
[0049] Figure 7 This is an electron microscope image of the zeolite sample synthesized in Comparative Example 4 of the present invention;
[0050] Figure 8 This is the XRD pattern of the chabazite with CHA structure synthesized in Example 1 of the present invention;
[0051] Fig. 9 This is the XRD pattern of the chabazite with CHA structure synthesized in Example 2 of the present invention;
[0052] Fig.10 This is the XRD pattern of the chabazite having a CHA structure synthesized in Example 3 of the present invention;
[0053] Fig.11 This is the XRD pattern of the chabazite having a CHA structure synthesized in Example 4 of the present invention;
[0054] Fig.12 This is the XRD pattern of the chabazite having a CHA structure synthesized in Example 5 of the present invention;
[0055] Fig.13 The XRD pattern of the NaY zeolite with FAU structure synthesized in Comparative Example 1 of the present invention;
[0056] Fig.14 This is the XRD pattern of the synthetic sample of Comparative Example 2 of the present invention;
[0057] Fig.15 This is the XRD diagram of the synthetic sample of Comparative Example 3 of the present invention;
[0058] Fig.16 This is the XRD diagram of the sample synthesized in Comparative Example 4 of the present invention. DETAILED DESCRIPTION
[0059] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the above content of the present invention.
[0060] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0061] The grades of the raw materials involved below are not limited, and chemical raw materials above industrial grade can meet the implementation of the technical solution of the present invention. The raw materials involved in the following embodiments and comparative examples are all industrial grade.
[0062] Evaluation and analysis methods:
[0063] Phase test conditions (X-ray diffraction analysis): light source CuKα, tube voltage 40kV, tube current 20mA. Scanning speed 10° / min, scanning range 2θ=4°-45°
[0064] Electron microscope test conditions: The crystal morphology analysis was performed using a scanning electron microscope (model JSM-IT200) produced by Japan Electronics Co., Ltd. JSM-IT200: The dried and ground sample was placed on the conductive glue, and then the processed sample was placed in a vacuum of 10 -2 The sample was purified under the condition of pa, and then the scanning test was carried out under the conditions of acceleration voltage 5kV and working distance 10mm.
[0065] Example 1
[0066] This embodiment provides a chabazite having a CHA structure, and the specific synthesis method is as follows:
[0067] 1) Weigh 162g of water glass, add 119g of high-basicity sodium aluminate thereto, stir evenly, and age at 35°C for 16h to obtain a NaY molecular sieve directing agent; the NaY molecular sieve directing agent has a ratio of 15.8Na 2 O:1.0Al 2 O 3 :14.4SiO 2 :317H 2 O.
[0068] 2) Weigh 165g of water glass, add 33g of the above-mentioned NaY molecular sieve directing agent, then add 70g of aluminum sulfate solution at a uniform speed over 45min, and finally add 35g of low-basicity sodium aluminate to adjust the proportion of each component. After homogenizing and stirring for 1h, a gel is obtained. The proportion of each substance in the gel is 2.1Na 2 O:1.0Al 2 O 3 :7.4SiO 2 :155H 2 O.
[0069] 3) Add 24 g of potassium hydroxide solid to the above gel, stir for 15 min, put into a sealed crystallization tank, crystallize at 94° C. for 15 h, filter, and wash with water to obtain sample S-1.
[0070] Example 2
[0071] This embodiment provides a chabazite having a CHA structure, and the specific synthesis method is as follows:
[0072] 1) Weigh 142g of water glass, add 105g of high-basicity sodium aluminate thereto, stir evenly, and age at 38°C for 16h to obtain a NaY molecular sieve directing agent. The NaY molecular sieve directing agent has a ratio of 12.6 Na 2 O:0.8Al 2 O 3 :11.4SiO 2 :252.8H 2 O;
[0073] 2) Weigh 165 g of water glass, add 24 g of the above-mentioned NaY molecular sieve directing agent, add 46 g of aluminum sulfate solution at a constant speed of 45 min, and then add 26 g of low-basicity sodium aluminate to adjust the ratio of each component. After homogenizing and stirring for 1 hour, a gel is obtained; the ratio of each substance in the gel is 3.6 Na 2 O:1.1Al 2O 3 :11.6SiO 2 :221.7H 2 O.
[0074] 3) Add 30 g of potassium hydroxide solid to the above gel, stir for 15 min, and then put into a sealed crystallization tank; crystallize at 100° C. for 32 h, filter, and wash with water to obtain sample S-2.
[0075] Example 3
[0076] This embodiment provides a chabazite having a CHA structure, and the specific synthesis method is as follows:
[0077] 1) Weigh 178g of water glass, add 121g of high-basicity sodium aluminate thereto, stir evenly, and age at 28°C for 40h to obtain a NaY molecular sieve directing agent. The NaY molecular sieve directing agent has a ratio of 17.6 Na 2 O:1.1Al 2 O 3 :17.0SiO 2 :361.6H 2 O;
[0078] 2) 139g of aluminum sulfate solution was added to 165g of water glass at a uniform speed for 1.5h, and then 26g of low-basicity sodium aluminate was added. After stirring for 30min, 140g of the above-mentioned NaY molecular sieve directing agent was added. After homogenous stirring for 1h, a gel was obtained; the proportion of each substance in the gel was 1.7Na 2 O:1.0Al 2 O 3 :6.1SiO 2 :154.2H 2 O:
[0079] 3) Add 52 g of potassium hydroxide solid to the above gel, stir for 15 min, and then put into a sealed crystallization tank; crystallize at 88° C. for 32 h, filter, and wash with water to obtain sample S-3.
[0080] Example 4
[0081] This embodiment provides a chabazite having a CHA structure, and the specific synthesis method is as follows:
[0082] 1) Weigh 15g of sodium hydroxide and add it to 127g of silica sol, then add 119g of high-basicity sodium aluminate to the mixture, stir evenly, and age at 30°C for 30h to obtain a NaY molecular sieve directing agent; the NaY molecular sieve directing agent has a ratio of 16.4Na 2 O:0.9Al 2 O 3 :13.6SiO2 :238.5H 2 O;
[0083] 2) Weigh 165 g of silica sol, add 60 g of the above-mentioned NaY molecular sieve directing agent, add 95 g of aluminum sulfate solution at a uniform rate for 1 hour, then add 36 g of low-basicity sodium aluminate, and stir homogenously for 2 hours to obtain a gel; the ratio of each substance in the gel is 3.0 Na 2 O:1.2Al 2 O 3 :9.8SiO 2 :171.2H 2 O.
[0084] 3) Add 25 g of potassium hydroxide solid to the above gel, stir for 30 min, and then put into a sealed crystallization tank; crystallize at 105° C. for 10 h, filter, and wash with water to obtain sample S-4.
[0085] Example 5
[0086] This embodiment provides a chabazite having a CHA structure, and the specific synthesis method is as follows:
[0087] 1) Weigh 162g of water glass, add 119g of high-basicity sodium aluminate thereto, stir evenly, and age at 35°C for 24h to obtain a NaY molecular sieve directing agent; the NaY molecular sieve directing agent has a ratio of 15.8Na 2 O:1.0Al 2 O 3 :14.4SiO 2 :317.0H 2 O;
[0088] 2) Weigh 165 g of water glass, add 55 g of the above-mentioned NaY molecular sieve directing agent, add 68 g of aluminum sulfate solution at a uniform rate for 1 hour, and then add 23 g of low-basicity sodium aluminate to adjust the proportion of each component. After homogenizing and stirring for 1 hour, a gel is obtained; the ratio of each substance in the gel is 2.0 Na 2 O:0.75Al 2 O 3 :6.6SiO 2 :139.2H 2 O;
[0089] 3) Add 45 g of potassium hydroxide solid to the above gel, stir for 15 min, and then put into a sealed crystallization tank; crystallize at 100° C. for 15 h, filter, and wash with water to obtain sample S-5.
[0090] Example 6
[0091] This embodiment provides a chabazite having a CHA structure, and the specific synthesis method is as follows:
[0092] 1) Weigh 86g of water glass, add 60g of high-basicity sodium aluminate thereto, stir evenly, and age at 35°C for 24h to obtain a NaY molecular sieve directing agent; the NaY molecular sieve directing agent has a ratio of 17.6Na 2 O:1.1Al 2 O 3 :16.7SiO 2 :355.0H 2 O;
[0093] 2) Weigh 330 g of water glass, add 45 g of the above-mentioned NaY molecular sieve directing agent, add 78 g of aluminum sulfate solution at a uniform rate for 1 hour, and then add 22 g of low-basicity sodium aluminate to adjust the proportion of each component. After homogenizing and stirring for 1 hour, a gel is obtained; the ratio of each substance in the gel is 5.4 Na 2 O: 1.25Al 2 O 3 :18.0SiO 2 :323H 2 O;
[0094] 3) Add 100 g of potassium hydroxide solid to the above gel, stir for 15 min, and then put into a sealed crystallization tank; crystallize at 100° C. for 15 h, filter, and wash with water to obtain sample S-6.
[0095] Comparative Example 1
[0096] This comparative example provides a zeolite, and the specific synthesis method is as follows:
[0097] 1) Weigh 162g of water glass, add 119g of high-basicity sodium aluminate thereto, stir evenly, and age at 35°C for 16h to obtain a NaY molecular sieve directing agent; the NaY molecular sieve directing agent has a ratio of 15.8Na 2 O:1.0Al 2 O 3 :14.4SiO 2 :317H 2 O.
[0098] 2) Weigh 165 g of water glass, add 33 g of the above molecular sieve directing agent, add 70 g of aluminum sulfate solution at a constant speed of 45 min, and then add 35 g of low-basicity sodium aluminate to adjust the ratio of each component. After homogenizing and stirring for 1 hour, a gel is obtained; the ratio of each substance in the gel is 2.1 Na 2 O:1.0Al 2 O 3 :7.4SiO 2 :155H 2 O.
[0099] 3) The gel was placed in a sealed crystallization tank; crystallized at 94° C. for 28 h, filtered, and washed with water to obtain sample C-1.
[0100] Comparative Example 2
[0101] This comparative example provides a zeolite, and the specific synthesis method is as follows:
[0102] 1) Weigh 162g of water glass, add 119g of high-basicity sodium aluminate thereto, stir evenly, and age at 35°C for 16h to obtain a NaY molecular sieve directing agent; the NaY molecular sieve directing agent has a ratio of 15.8Na 2 O:1.0Al 2 O 3 :14.4SiO 2 :317H 2 O.
[0103] 2) Weigh 165 g of water glass, add 33 g of the above-mentioned NaY molecular sieve directing agent, add 24 g of potassium hydroxide solid, stir for 15 min, add 70 g of aluminum sulfate solution at a constant speed for 45 min, and then add 35 g of low-basicity sodium aluminate to adjust the ratio of each component. After homogenizing and stirring for 1 h, a gel is obtained. The ratio of each substance in the gel is 2.1 Na 2 O:1.0Al 2 O 3 :7.4SiO 2 :155H 2 O: 3.2K 2 O; the gel was placed in a sealed crystallization tank, crystallized at 94°C for 15 hours, filtered, and washed with water to obtain sample C-2.
[0104] Comparative Example 3
[0105] This comparative example provides a zeolite, and the specific synthesis method is as follows:
[0106] 1) Weigh 162g of water glass, add 119g of high-basicity sodium aluminate thereto, stir evenly, and age at 35°C for 16h to obtain a NaY molecular sieve directing agent; the NaY molecular sieve directing agent has a ratio of 15.8Na 2 O:1.0Al 2 O 3 :14.4SiO 2 :317H 2 O;
[0107] 2) Weigh 234 g of water glass, add 39 g of the above-mentioned NaY molecular sieve directing agent, then add 35 g of aluminum sulfate solution at a uniform speed over 45 min, and finally add 39 g of low-basicity sodium aluminate to adjust the ratio of each component. After homogenizing and stirring for 1 h, a gel is obtained; the ratio of each substance in the gel is 9.0 Na2 O:1.3Al 2 O 3 :20.0SiO 2 : 320H 2 O;
[0108] 3) Add 12 g of potassium hydroxide solid to the above gel, stir for 15 min, put into a sealed crystallization tank, crystallize at 94° C. for 15 h, filter, and wash with water to obtain sample C-3.
[0109] Comparative Example 4
[0110] This comparative example provides a zeolite, and the specific synthesis method is as follows:
[0111] 1) Weigh 162g of water glass, add 119g of high-basicity sodium aluminate thereto, stir evenly, and age at 35°C for 16h to obtain a NaY molecular sieve directing agent; the NaY molecular sieve directing agent has a ratio of 15.8Na 2 O:1.0Al 2 O 3 :14.4SiO 2 :317H 2 O;
[0112] 2) Weigh 165 g of water glass, add 33 g of the above-mentioned NaY molecular sieve directing agent, then add 70 g of aluminum sulfate solution at a uniform speed over 45 min, and finally add 35 g of low-basicity sodium aluminate to adjust the ratio of each component. After homogenizing and stirring for 1 hour, a gel is obtained; the ratio of each substance in the gel is 2.1 Na 2 O:1.0Al 2 O 3 :7.4SiO 2 :155H 2 O;
[0113] 3) Add 7.5 g of potassium hydroxide solid to the above gel, stir for 15 min, put into a sealed crystallization tank, crystallize at 94° C. for 15 h, filter, and wash with water to obtain sample C-4.
[0114] The samples prepared in the above examples and comparative examples were respectively subjected to electron microscope scanning, as shown in FIG. Figure 1-7 As shown by Figure 1-5 It can be seen that the crystal structure of the zeolite sample provided by the present invention is spherical, the outer surface is similar to a ball of wool, the grains are not agglomerated, and the size is 2 to 3 μm, indicating that it is a chabazite with a CHA structure. Figure 6It can be seen that the zeolite is a Y-type molecular sieve of faujasite, and the crystal size is 300-400nm, indicating that the sample prepared in Comparative Example 1 is a NaY zeolite with a FAU structure, not a chabazite with a CHA structure; it can be seen that if potassium hydroxide is not added, under the same conditions, if potassium hydroxide is not added, chabazite with a CHA structure cannot be prepared. Figure 7 It can be seen that the crystals of the zeolite molecular sieve obtained in Comparative Example 4 have both the crystal appearance of Y-type molecular sieve and the crystals of chabazite, indicating that when the amount of potassium hydroxide added is low, the molecular sieve obtained is not a pure phase of chabazite.
[0115] The zeolite samples prepared in the above examples and comparative examples were subjected to X-ray diffraction (XRD) analysis and testing, as shown in FIG. Figures 8 to 16 As shown. Figures 8 to 12 It can be seen that the samples prepared by the preparation method provided by the present invention have 2θ=8.6-9.0°, 12.6-13.0°, 17.7-2-17.1°, 20.4-20.8°, 21.9-22.3°, 28.4-28.8°, 24.7-25.1°, and 38.8-39.2°, which are all typical diffraction peaks of CHA structure chabazite, indicating that they all have CHA structure, which is consistent with the results of electron microscope scanning. Fig.13 It can be seen that 2θ=6.2°, 10.1°, 11.9°, 15.6°, 18.7°, 20.4°, 23.6°, 27.0°, 31.4°, 34.8°, and 37.9° are typical XRD diffraction peaks of Y-type molecular sieves, indicating that the sample prepared in Comparative Example 1 is a NaY zeolite with a FAU structure, which is consistent with Figure 6 The results are consistent with those of Fig.14 and Fig.15 It can be seen that the XRD test results have no characteristic diffraction peaks, indicating that they are all amorphous structures without any crystal form, indicating that the samples prepared in Comparative Examples 2-3 are not chabazite and do not have a CHA structure. Fig.16 It can be seen that the XRD results show that the characteristic diffraction peaks of the sample prepared in Comparative Example 4 include both Y-type zeolite and chabazite, and the obtained structure is a mixed crystal molecular sieve.
[0116] Example 6 used the same method to carry out electron microscope scanning and XRD testing respectively. The results of electron microscope scanning were consistent with those of Figure 1-5 Basically the same: the crystal structure is spherical, the outer surface is similar to a ball of wool, the grains are not agglomerated, and the size is 2 to 3 μm; the XRD test results are the same as Figure 8-12 The results are basically the same, with typical diffraction peaks of CHA structure chabazite, that is, the product prepared in Example 6 is chabazite with CHA structure.
[0117] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.
Claims
1. A method for synthesizing chabazite having a CHA structure, characterized in that: The steps include: Step 1, mixing a silicon source and an aluminum source, or a silicon source, an aluminum source and sodium hydroxide, and aging the mixture to obtain a NaY molecular sieve directing agent; Step 2, mixing a silicon source, an aluminum source and the NaY molecular sieve directing agent to form a gel; Step 3, after uniformly mixing the gel and potassium hydroxide, crystallizing for 10 to 40 hours, separating and washing, to obtain the chabazite having a CHA structure; Calculated as oxides, the molar ratio of each substance in the NaY molecular sieve directing agent is (10-18) SiO2: (0.7-1.3) Al2O3: (10-18) Na2O: (200-400) H2O; Calculated as oxides, the molar ratio of the substances in the gel is (1-6) Na2O: (0.7-1.3) Al2O3: (5-18) SiO2: (100-350) H2O; The mass ratio of the potassium hydroxide to the gel is (6-25):
100.
2. The synthesis method according to claim 1, characterized in that The crystallization time is 10 to 35 hours.
3. The synthesis method according to claim 1, characterized in that The crystallization temperature is 85-110°C.
4. The synthesis method according to claim 1, characterized in that The mass ratio of the NaY molecular sieve directing agent and the gel is (3-30):100, calculated based on Al2O3.
5. The synthesis method according to claim 1, characterized in that In step 1, the aging temperature is 25-40° C., and the aging time is 6-42 hours, preferably 15-40 hours.
6. The synthesis method according to claim 1, characterized in that In step 2, after the silicon source and the NaY molecular sieve directing agent are mixed, the aluminum source is added at a uniform speed within 0.5 to 4 hours, and after the aluminum source is added, homogenization is performed to obtain the gel.
7. The synthesis method according to claim 1, characterized in that The silicon source is selected from an organic silicon source or an inorganic silicon source, preferably an inorganic silicon source, and more preferably at least one of water glass, silica sol and silica gel.
8. The synthesis method according to claim 1, characterized in that The aluminum source is selected from an organic aluminum source or an inorganic aluminum source, preferably an inorganic aluminum source, and more preferably at least one of aluminum sulfate, sodium aluminate and sodium metaaluminate.
Citation Information
Patent Citations
A method for preparing chabazite and chabazite membrane
CN102285666A
Synthetic method of chabasite
CN102442679B
Method for direct hydrothermal synthesis of chabasite with intermediate silica-alumina ratio
CN106145137A
A method for synthesizing zeolite molecular sieves with chabazite structure
CN106145138B
Internal combustion engine tail gas cleaning treatment catalyst and preparation method thereof
CN106145139A
Cited By
Method for synthesizing K-CHA zeolite from lithium slag
CN121609352A
A method for synthesizing k-cha zeolite from lithium slag
CN121609352B